THE EFFECTS OF FINANCIAL LEVERAGE AND OPERATING LEVERAGE TOWARDS PROFITABILY - Pertiwi Hari Sandi, Santi; Mulyadi, Dedi; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to obtain empirical evidence and find clarity of phenomena and conclusions about the influence of the two variables mentioned above towards profitability of Property and Real Estate Companies Listed in the Indonesia Stock Exchange for The Period of 2013-2017. The research was conducted using descriptive methods. This type of research is quantitative research. The study population comes from all Property and Real Estate Companies Listed on The Indonesia Stock Exchange for The Period of 2013-2017, the sampling technique uses a purposive sampling method and based on the criteria selected 41 research samples on property and real estate companies for the period 2013-2017. Testing on the research hypothesis used multiple linear regression analysis techniques. The result of the study indicates that financial leverage has a partial effect on earnings per share; operating leverage does not partially effect on earnings per share; financial leverage and operating leverage together or simultaneously have a significant effect on profitability (earning per share) of a Property and Real Estate Companies Listed on The Indonesia Stock Exchange for The Period 2013-2017.